Determination of the Effect of Hallufix Splint on Hallux Valgus Angle in Subjects with Mild and Moderate Hallux Valgus Compared with Night Splint: A Double-Blind Clinical Trial - Tahmoores Tahmasbi; Atefe Rahimi; Bahareh Aminzade-Sede (Vesnu Publications, 2017)
metatarsophalangeal (MTP) joint due to lateral deviation of the great toe and medial deviation of the first metatarsal bone. The most common interventions in cases with mild to moderate deformity is the use of orthosis which includes two types of splints, dynamic splint for daily use and static splint to be used during the night. The aim of this study was to compare the effect of hallufix dynamic splint on hallux valgus angle in subjects with mild and moderate hallux valgus with night splint. Materials and Methods: This quasi-experimental study was conducted on 34 subjects who had referred to orthopedic specialists in Isfahan and the surrounding towns, Iran, with complaints of hallux valgus . These subjects were divided into two groups of 17 people that were matched in terms of age, gender, and degree of deformity. Then, one group was given night splint and the other group hallufix splint, randomly. Hallux valgus angle was measured using anterior-posterior weight bearing radiograph at baseline and after 6 weeks of orthosis use. Results: The results showed that the use of both orthoses reduced the hallux valgus angle, but this reduction was not statically significant (P > 0.05). In addition, the effect of both splints on the reduction of hallux valgus angle was similar (P = 0.97). Conclusion: The use of night splint and hallufix dynamic splint for 6 weeks did not cause any improvement in hallux valgus angle.